Capital Fulfillment Strategy For Trigona Honey Bee Smes In Balangan Sembung Village, Mengwi District, Badung Regency - Ni Made Rustini; I Ketut Selamet; A. A. Sri Purnami (International Journal Of Community Service, 2023)
Bali has started to develop honey bee cultivation of the stingless bee type. The type of honey bee that is widely cultivated by the people of Bali is the Trigona laevicep species known as "snake-kele" The cultivation of the honey bee kele-kele (Trigona Sp) is now being eyed by the public, because the results of this beekeeping are very promising, while in terms of investment costs it is not too big and this bee doesn't sting. Br Balangan, Sembung village, is one of the villages that has been cultivating honey bees, but they do not understand how efforts should be made to increase the number of bee colonies due to limited capital. Through the addition of bee colonies, it is hoped that the amount of production will increase and be profitable in the long term. In response to this, the University of Waradewa Community Service team provided assistance with the Strategy for fulfilling UKM Capital for the group of honeysuckle beekeepers at Br. Balangan, Sembung Village, Mengwi District, Badung Regency.. Honey is a commodity from non-timber forest products (HHBK) which has many benefits, and there is quite a high demand for consumer honey for catfish honey, but currently the production of honey is still low due to a lack of colonies/ nest of sorrel. Breeders need to add more colonies by buying plots of catfish that already have queens from Kalimantan. In order to increase the capital of the breeders, it is necessary to provide assistance in determining the Strategy for fulfilling the Capital for UKM Honey Bees Trigona Sp. in Br. Balangan. Through the fulfillment of capital, honey production can increase so that Br. Balangan becomes a village producing catfish honey.